2013
DOI: 10.1142/s0218301313500766
|View full text |Cite
|
Sign up to set email alerts
|

Ground State Magnetic Properties of Odd Neutron Dy Isotopes

Abstract: Using the quasiparticle phonon nuclear model (QPNM) and taking into account the spin–spin interaction, the effects of the spin polarization on spin gyromagnetic factors (gs) as well as the intrinsic magnetic moments (gK) of the deformed odd neutron 155-165 Dy isotopes were studied. The calculated values of gs and gK are in fair agreement with the experiment as well as with other microscopic calculations. Our calculations indicated that because of the core polarization, the gs factors of the nucleons in the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…Recently, using the QPNM [7][8][9][10] we have developed a method to investigate the spin polarization effects on the groundstate magnetic properties of odd-mass nuclei for the first time. The demonstration of the method was made with numerical calculations in 157−167 Er [11] and 155−165 Dy [12] isotope chains. The results of our previous work [11,12] have indicated that the QPNM interpretation of the magnetic moments seems most appropriate, so at present it represents the only possible approach to an improved understanding of the spin renormalization effects experimentally observed for the magnetic dipole moments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, using the QPNM [7][8][9][10] we have developed a method to investigate the spin polarization effects on the groundstate magnetic properties of odd-mass nuclei for the first time. The demonstration of the method was made with numerical calculations in 157−167 Er [11] and 155−165 Dy [12] isotope chains. The results of our previous work [11,12] have indicated that the QPNM interpretation of the magnetic moments seems most appropriate, so at present it represents the only possible approach to an improved understanding of the spin renormalization effects experimentally observed for the magnetic dipole moments.…”
mentioning
confidence: 99%
“…The demonstration of the method was made with numerical calculations in 157−167 Er [11] and 155−165 Dy [12] isotope chains. The results of our previous work [11,12] have indicated that the QPNM interpretation of the magnetic moments seems most appropriate, so at present it represents the only possible approach to an improved understanding of the spin renormalization effects experimentally observed for the magnetic dipole moments. Therefore, it would be important to expand the calculations on other isotope chains to test if the method can reproduce the intrinsic magnetic moment ( K ) and the effective spin factor ( ) observed in other rare-earth nuclei.…”
mentioning
confidence: 99%
“…Since spin-spin residual interactions play an active role in renormalization of g s factors, we take into account spindependent interactions in our calculations. The results obtained reveal that spin interactions allow to successfully explain the spin polarization phenomenon observed in odd-mass nuclei and its effects on ground-state magnetic properties [1][2][3]. The applications in physics have been mostly in the field of general and differential equation [42][43][44].…”
Section: K πmentioning
confidence: 85%
“…In this method, the spin-spin interaction parameter is obtained by comparing the calculated ground-state intrinsic magnetic moment (gK) with the experimental value of the odd-mass nucleus. Method were successfully applied to explain the ground state magnetic properties of 157−167 Er, 165 Dy, 165−179 Hf, 137−145 Ce, Ho, 239 Pu, 183,185 W, 185,187 Re and 187,189 Os [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…of this configuration for the neutron and proton, as was pointed out by Hisatake [4], are identified as 3/2 and 5/2, respectively. The determination of the Nilsson quantum numbers of ground state of the odd-odd 138,140 Pr nuclei will serve as a basis for calculating various characteristics such as beta decay [11], magnetic moment [12][13][14][15][16] and magnetic dipole transitions [17][18][19][20][21][22][23] of even and odd mass nuclei.…”
Section: Expected Ground State Configuration For 140 Prmentioning
confidence: 99%